2021
DOI: 10.1186/s13643-020-01560-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexual dysfunction in men with multiple sclerosis: a systematic review and meta-analysis

Abstract: Background Symptoms in multiple sclerosis (MS) can lead to different types and ranges of sexual dysfunction in MS patients. Studies in different parts of the world have reported a high range of sexual dysfunction in men with MS. This study aimed to estimate pooled prevalence of sexual dysfunction in men with MS. Methods The authors searched Web of Science, PubMed, Scopus, Embase, Magiran, SID, and Iran Medical Papers Database using the keywords “mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…It is likely that the particular research context (e.g. see Pham et al ., 2021 1 ) will have a large degree of influence on the performance metrics to be had if they can be determined. The description of how the 17 “Key items of interest” were determined and if there is a plan to put these forth as methodological guidelines or a reporting checklist would be helpful.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the particular research context (e.g. see Pham et al ., 2021 1 ) will have a large degree of influence on the performance metrics to be had if they can be determined. The description of how the 17 “Key items of interest” were determined and if there is a plan to put these forth as methodological guidelines or a reporting checklist would be helpful.…”
mentioning
confidence: 99%
“…It is likely that the particular research context (e.g. see Pham et al ., 2021 1 ) will have a large degree of influence on the performance metrics to be had if they can be determined.…”
mentioning
confidence: 99%
“…Lisa B. Grech 1,2* , Michelle Allan 3 and Barbora de Courten 1 We read with interest the review by Dastoorpoor and colleagues [1], highlighting the prevalence of sexual dysfunction in men with multiple sclerosis (MS). We congratulate the authors on bringing together research on the important topic of the high prevalence of sexual dysfunction, which may be caused, at least in part, by the high prevalence of psychological symptoms in MS, but may also precipitate or compound existing psychological symptoms and impact quality of life.…”
Section: Sexual Dysfunction In Men With Multiple Sclerosismentioning
confidence: 99%
“…A Danish community study found that 11% of male respondents reported sexual dysfunction (frequent and perceived as a problem), while 68% of males reported less severe sexual difficulties [5]. Many of the studies included in the review by Dastoorpoor and colleagues [1] reported on the severity, enabling a qualitative synthesis and discussion. Primary, secondary and tertiary causal aspects of sexual dysfunction were also reported in many of the included studies, again providing an opportunity for a nuanced discussion about the causal impact attributable to MS disease processes, the symptoms of MS or comorbid factors.…”
Section: Sexual Dysfunction In Men With Multiple Sclerosismentioning
confidence: 99%
“…Syst Rev. 2021 Jan 26;10(1):39. doi: 10.1186/s13643-020-01542-z) 1 . For example, item 5 of PRIMSA-S – Citation searching - states “Citation searching 5 Indicate whether cited references or citing references were examined, and describe any methods used for locating cited/citing references (e.g., browsing reference lists, using a citation index, setting up email alerts for references citing included studies).” I think this is important so as not to potentially confuse readers.…”
mentioning
confidence: 99%